Early phenotypic activation of circulating helper memory T cells in scleroderma: correlation with disease activity. Issue 4 (April 1993) - Fiocco, U; Rosada, M; Cozzi, L; Ortolani, C; De Silvestro, G; Ruffatti, A; Cozzi, E; Gallo, C; Todesco, S
Abstract : OBJECTIVES--The differential expression of several accessory/activation molecules (CD26, CD29, CD45RA, CD25, MLR4, HLA-DR) on peripheral blood CD4+ and CD8+ T lymphocytes in patients with scleroderma was compared with that in controls and patients with other connective systemic diseases to look for evidence of the involvement of T cells in the disease process of scleroderma. METHODS--The two colour expression of surface molecules by circulating T cells was analysed with a panel of monoclonal antibodies and flow cytometry in 17 patients with scleroderma, 10 patients with systemic lupus erythematosus, and five patients with rheumatoid arthritis, and the results compared with those for 10 normal controls. The two colour T CD4+ phenotype was further compared between patients with active and quiescent disease in these patients with scleroderma. The coexpression of surface molecules by CD4+ T cells was also analysed by three colour flow cytometry in eight patients with scleroderma. RESULTS--Patients with scleroderma showed increased CD4+CD26+ and CD4+CD25+ percentages and absolute numbers and decreased CD8+CD29+ percentages compared with controls. Moreover, a significant correlation between the higher CD4+CD26+ T cell percentage and absolute cell numbers with disease activity was observed. Most of the CD4+ peripheral blood T cells from patients with scleroderma showed the CD26+CD45RA- phenotype by three colour flow cytometry analysis. CONCLUSIONS--The distinctive pattern of early helper memory T cell activation in these patients with rapidly evolving scleroderma supports the role of a T cell mediated mechanism in the progression of scleroderma.